2021
DOI: 10.2174/1386207323666200717150414
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Effects of Sulfur Mustard on Skin and its Current Treatments: Possible Application of Phytochemicals

Abstract: Background: Sulfur-(SM) and nitrogen (NM)-based mustards are mutagenic incapacitating compounds that are widely used in vesicating chemical warfare and cause toxicity in many organs especially skin. SM, as a potent vesicating agent, contributes to the destruction of skin in dermis and epidermis layers. The progression of lesion is dependent on the concentration of SM and duration of exposure. Body responses start with pruritus, erythema, edema and xerosis, which lead to the accumulation of immune cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 143 publications
0
0
0
Order By: Relevance
“…Since ROS formation and DNA damage, as well as DNA damage sensing, are interconnected (reviewed in (Srinivas et al, 2019)), the antioxidant property of carvedilol may be an alternative mechanism underlying the protective effect against NM. Supporting the ROS hypothesis, many studies reported ROS scavengers as experimental treatments for vesicant exposure (Bobb et al, 2005;Etemad et al, 2019;Hassanpour et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since ROS formation and DNA damage, as well as DNA damage sensing, are interconnected (reviewed in (Srinivas et al, 2019)), the antioxidant property of carvedilol may be an alternative mechanism underlying the protective effect against NM. Supporting the ROS hypothesis, many studies reported ROS scavengers as experimental treatments for vesicant exposure (Bobb et al, 2005;Etemad et al, 2019;Hassanpour et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…The early NM-induced inflammatory and apoptotic mechanisms depend on p53 (Inturi et al, 2013). Although several studies have focused on anti-inflammatory drugs and natural products against mustards over the past few decades (Bobb et al, 2005;Etemad et al, 2019;Hassanpour et al, 2021), no satisfactory therapeutic outcomes have been reported. One major limitation is the lack of knowledge of the specific mechanisms underlying NM-induced cutaneous inflammation.…”
Section: Introductionmentioning
confidence: 99%